PERBAIKAN KUALITAS PELAYANAN PADA LAYANAN PERAWATAN LIFT DAN ESKALATOR DENGAN METODE SERVQUAL-IPA-HOQ - Dabith Ghazali (Universitas Mercu Buana, 2017)
In an effort to improve the competitiveness of the company, an approach is needed to determine customer expectations. This study aims to determine service characteristics that have not met customer expectations and provide advice on improving the quality of care services for elevators and escalators. The method used is ServQual to measure customer expectations and perceptions. Information was collected through a questionnaire in the research focus group. The results of this study are a number of 21 indicators in 5 dimensions of ServQual showing customer expectations greater than customer perceptions. Then continued observation and interviews with the management to make technical responses in an effort to improve service quality. The findings in this study can help management in improving service quality to improve customer satisfaction.